A COMPARATIVE STUDY OF MPPT STRATEGIES AND A NOVEL SINGLE-PHASE INTEGRATED BUCK-BOOST INVERTER FOR SMALL WIND ENERGY CONVERSION SYSTEMS - Pena, Jose C. U. [UNESP]; Brito, Moacyr A. G. de [UNESP]; A e Melo, Guilherme de [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2011)
This paper presents the analysis of some usual MPPT (Maximum Power Point Tracking) strategies intended for small wind energy conversion (up to 1kW) based on permanent magnet synchronous generators (PMSG), considering the stand-alone application for a novel buck-boost integrated inverter. Each MPPT method is analytically introduced and then it is simulated using MatLab/Simulink (R) considering standard conditions of wind and also commercially available turbines and generators. The extracted power in each case is compared with the maximum available power, so the tracking factor is calculated for each method. Thus, the focus is on the application to improve the efficiency of stand-alone wind energy conversion systems (WECS) with battery chargers and AC load supplied by inverter. Therefore, for this purpose a novel single phase buck-boost integrated inverter is introduced. Finally, the main experimental results for the introduced inverter are presented.
Keywords: MPPT for small WECS; Small WECS with PMSG; Integrated Buck-Boost Inverters; Renewable Energy Sources; Wind Energy